Estimated losses in soybean (Glycine max (L.) Merril) harvest according to the speed and rotation of the trail system - Souza, Jarlyson Brunno Costa [UNESP]; Passos, Mádilo Lages Vieira; da Silva, Eduardo Arouche; de Brito Filho, Armando Lopes [UNESP]; de Almeida, Samira Luns Hatum [UNESP]; da Silva Oliveira, Ana Karla; de Sousa Ferreira, Lusiane; da Silva Sousa, Washington; Almeida, Edmilson Igor Bernardo; da Silva, Rouverson Pereira [UNESP] (Southern Cross Publishing, 2021)
The soybean crop (Glycine max. (L.) Merril) shows strong participation in the Brazilian economy. Therefore, the aim of the present study was to quantify the losses in the cutting and feeding platform and in the trail system in mechanized soybean harvest by analyzing different speed and rotation adjustments of the trailing cylinder. The experiment was carried out in a commercial soybean plot on a farm located in the municipality of Brejo (MA), during the 2017/2018 harvest. The harvester evaluated was a Case IH 8120, with a maximum power of 34.2 kW, axial flow system, and 12.2-m platform equipped with a conveyor system (draper). The experiment was conducted in two different areas. Area 1 was planted with the Brasmax® Opus (BMX Opus) cultivar, while area 2 was cultivated with the BRS 9383 cultivar. The treatments consisted of three machine speeds (4 km h-¹, 6 km h-¹, and 7 km h-¹), associated with the rotation levels of 500 rpm and 800 rpm in the trail system. The experimental design used was randomized blocks in a 3 x 2 factorial arrangement, with four replications. For the BMX Opus cultivar, harvest losses did not influence the travel speeds and rotations evaluated in the experiment due to the marked instability within the treatments. The BRS 9383 cultivar showed satisfactory results at a speed of 4 km h-1 combined with a rotation of 800 rpm, which obtained acceptable numbers for the soybean harvest (54.09 kg ha-1).
Keywords: Agricultural mechanization; productivity; smart harvest; trailing cylinder; waste